Design of chirp waveforms for multiple-access ultrasonic indoor positioning - Mohammad Omar Khyam (2020)
In ultrasonic positioning systems (UPSs) chirp waveforms have attracted much attention due to its high range resolution. However, the multiple-access schemes for the chirp-based UPS are limited. In its application to multiple-access ultrasonic positioning, effective waveform diversity design is a prerequisite. In a multiple-access UPS, each transmitter should transmit a unique waveform with impulse-like auto-correlation and relatively flat cross-correlations to the waveforms transmitted by other transmitters. Proposed in this paper is a methodology whereby multiple transmitters can transmit chirp signals simultaneously. The chirp waveforms are constructed by concatenating a number of linear sub-chirps of the same durations and bandwidths but different starting and stopping frequencies. This process is optimized by selecting sequences with impulse-like auto-correlations and relatively flat cross-correlations. First, the efficiency of the proposed methodology is evaluated by several metrics and, then, in an indoor environment, through simulations and experiments for ultrasonic positioning.